Evaluation of a 7050-TAF aluminum alloy submitted to creep age forming - Costa Junior,Paulo Roberto (2014)
CAF process combines creep and precipitation hardening which are highly dependent on time and temperature. The aging cycle relax the stresses induced during the loading phase. At the end of the process stress relaxation induces shape changes in the part but significant spring back is observed (about 70%). Usually CAF cycles for 7XXX alloys use times around 20 h and temperatures in the range of 120°C to 190°C. In the present work CAF tests were performed using the alloy 7050 in an intermediate condition named Temper to Age Forming (TAF). Using the alloy 7050-TAF resulted in significant process time reduction. From TAF temper, only 8 hours are necessary to achieve properties comparable to T74. Coupons were submitted to CAF in two levels of initial stress, 190 MPa and 290 MPa, resulting in spring back values of 70% and 60 % respectively. In addition, constant load creep tests were performed in the same stress levels and time of CAF tests to find the creep strain values. Creep tests performed under 190 MPa resulted in strain values around 0,1% after 8 h. On the other hand creep tests performed under 290 MPa failed after 7 h with creep strain values of 1,7%. Results obtained are close to that found in previous studies and it is possible to conclude that the use of alloy 7050 in TAF condition allows CAF to be done in 8 hours, since the initial stress is lower than 290 MPa.